Comparison and interpretation of freshwater bacterial structure and interactions with organic to nutrient imbalances in restored wetlands - Zheng, Fuchao; Zhang, Tiange; Yin, Shenglai; Qin, Ge; Chen, Jun; Zhang, Jinghua; Zhao, Dehua; Leng, Xin; An, Shuqing; Xia, Lu (Frontiers in Microbiology, 2022)
Chemical oxygen demand to nitrogen (COD/N) and nitrogen to phosphorus (N/P) ratios have distinct effects on bacterial community structure and interactions. However, how organic to nutrient imbalances affect the structure of freshwater bacterial assemblages in restored wetlands remains poorly understood. Here, the composition and dominant taxa of bacterial assemblages in four wetlands [low COD/N and high N/P (LH), low COD/N and low N/P (LL), high COD/N and high N/P (HH), and high COD/N and low N/P (HL)] were investigated. A total of 7,709 operational taxonomic units were identified by high throughput sequencing, and Actinobacteria, Proteobacteria, and Cyanobacteria were the most abundant phyla in the restored wetlands. High COD/N significantly increased bacterial diversity and was negatively correlated with N/P (R2 = 0.128; p = 0.039), and the observed richness (Sobs) indices ranged from 860.77 to 1314.66. The corresponding Chao1 and phylogenetic diversity (PD) values ranged from 1533.42 to 2524.56 and 127.95 to 184.63. Bacterial beta diversity was negatively related to COD/N (R2 = 0.258; p < 0.001). The distribution of bacterial assemblages was mostly driven by variations in ammonia nitrogen (NH4+-N, p < 0.01) and electrical conductivity (EC, p < 0.01), which collectively explained more than 80% of the variation in bacterial assemblages. However, the dominant taxa Proteobacteria, Firmicutes, Cyanobacteria, Bacteroidetes, Verrucomicrobia, Planctomycetes, Chloroflexi, and Deinococcus-Thermus were obviously affected by variation in COD/N and N/P (p < 0.05). The highest node and edge numbers and average degree were observed in the LH group. The co-occurrence networkindicated that LH promoted bacterial network compactness and bacterial interaction consolidation. The relationships between organic to nutrient imbalances and bacterial assemblages may provide a theoretical basis for the empirical management of wetland ecosystems.